Approaches and tools for inclusive value chain development: lessons from Uganda for improved impact - Naziri, D.; Mayanja, S.; Ssemwanga, J.; Donovan, J. (Practical Action Publishing, 2017)
Value chain development (VCD) with smallholders forms a central element of the poverty reduction strategies of governments and NGOs in developing countries. Nevertheless, too little is known about how VCD interventions are designed and implemented, the approaches and tools used, and the challenges faced in the process. This paper helps to fill this gap with evidence from six cases in Uganda. For each case, data was collected from interviews with NGOs, government organizations, buyers, and smallholder business organizations. Results indicate that use of available VCD guides and tools facilitated productive partnerships among chain actors, engagement with support organizations, and feedback mechanisms on intervention processes. Results also challenge NGOs, government agencies, and researchers to better understand the circumstances of resource-poor chain actors, the implications of VCD on gender relations, and the cultural and business context when designing and implementing VCD. This calls for stakeholders to employ a broader approach to VCD, using a combination of available and new tools, and to seek out deeper collaboration with key actors within and outside the value chain.